2015
DOI: 10.3892/ijo.2015.3202
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits cancer-associated fibroblast-driven prostate cancer invasion through MAOA/mTOR/HIF-1α signaling

Abstract: Cancer-associated fibroblasts (CAFs) are key determinants in the malignant progression of cancer, supporting tumorigenesis and metastasis. CAFs also mediate epithelial to mesenchymal transition (EMT) in tumor cells and their achievement of stem cell traits. Curcumin has recently been found to possess anticancer activities via its effect on a variety of biological pathways involved in cancer progression. In this study, we found that CAFs could induce prostate cancer cell EMT and invasion through a monoamine oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 61 publications
3
71
0
Order By: Relevance
“…We and others have previously demonstrated that CAF‐induced EMT is dependent on a proinflammatory signaling leading to HIF1α stabilization in normoxic condition (Du et al, ; Gandellini et al, ; Giannoni et al, ; Luo et al, ). By an, in silico analysis of miR‐1247 promoter we highlighted the existence of three hypoxia responsive elements and three HIF1α ancillary sequence binding site (Supporting Information Figure 1a).…”
Section: Resultsmentioning
confidence: 88%
“…We and others have previously demonstrated that CAF‐induced EMT is dependent on a proinflammatory signaling leading to HIF1α stabilization in normoxic condition (Du et al, ; Gandellini et al, ; Giannoni et al, ; Luo et al, ). By an, in silico analysis of miR‐1247 promoter we highlighted the existence of three hypoxia responsive elements and three HIF1α ancillary sequence binding site (Supporting Information Figure 1a).…”
Section: Resultsmentioning
confidence: 88%
“…IL-6 is expressed principally in T cells, fibroblast, macrophages, and mast cells; however, it could also be detected interacting with its receptor in prostatic cells [18]. Miličević et al in 2015 showed that IL-6 is expressed in epithelial and basal prostatic cells from normal, prostatic, and BPH and in premalignant and malignant epithelial cells as well as in some stromal cells [19].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the signals resulting from the downstream of this interconnection can lead to the self‐renewal of cancer cells and make them resistant to apoptosis by activating the anti‐apoptotic PI3K/AKT pathway . Additionally, the signals resulting from this interaction can increase the expression of HIF and activate the matrix metalloproteinases (MMP), which altogether enhance angiogenesis and the movement of cancer cells from their origin to other sites . In general, CXCR4 and CXCL12 factors in cancer patients can be used as diagnostic markers to evaluate the differentiation rate of MSC‐derived CAF cells (Figure ).…”
Section: The Role Of Chemokines In Pre‐metastatic and Metastatic Nichesmentioning
confidence: 99%